Kampanye Sosial Untuk Perubahan Sikap Mahasiswa Universitas Dharma Andalas Terhadap Sampah Botol Minuman Plastik - Mutiara Cahaya Regita; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
Plastic waste, especially single use plastic beverage bottles, poses a significant challenge in environmental conservation efforts. This study aims to design and implement a social campaign to change the attitudes od Dharma Andalas University students towards the use single use plastic bottles through the circular economy concept. The methods used in this campaign include distributing brochures, installing banners, interpersonal communication, focus discussion group (FGD), and creating educational content on social medi instagram. Tthe evaluation results show that the campaign successfully increased students awareness of the negative environmental impacts of plastic bottle waste. As many as 85,7% of students stated that this campaign had a significant influence on their behavior change in reducing the use of single use plastic bottles and switching to reusable water bottles (tumbler). This social campaign demonstrates that effective communication strategies can drive environmental friendly attitude and behavior changes among university students.